2013
DOI: 10.1103/physrevb.88.085418
|View full text |Cite
|
Sign up to set email alerts
|

Polarization discontinuity induced two-dimensional electron gas at ZnO/Zn(Mg)O interfaces: A first-principles study

Abstract: The discovery of a high-mobility two-dimensional electron gas (2DEG) in wurtzite ZnO/Zn(Mg)O heterostructures is promising for applications due to the high mobility of the carriers. In this paper, we study the formation and properties of the 2DEG at ZnO/Zn(Mg)O interfaces using first-principles calculations based on hybrid density functional theory. The 2DEG arises from the polarization discontinuity at the interface between the two materials. The uncompensated bound charge at the interface gives rise to an el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 53 publications
(88 reference statements)
1
24
0
Order By: Relevance
“…The fraction of exact exchange (0.375) adjusted to yield the experimental low temperature bandgap of 3.43 eV for ZnO 19 yields the bandgap of 10.2 eV for BeO, which is close to the experimental value of 10.6 eV, 20 and 7.72 eV for the stable rock-salt phase of MgO, close to the measured bandgap of 7.7 eV. 21 Based on the good agreement of calculated bulk binary bandgaps with experiment, a common value of 0.375 was adopted in this work for the exact exchange 22 fraction with the expectation that reasonable All calculations were performed using supercells with 72 atoms and using C-point eigenvalues only, and projector augmented wave (PAW) pseudopotentials. Wurtzite lattice was used throughout the work for all alloy compositions, which leads to an additional error at high concentrations of Mg, where rock-salt crystal structure would prevail.…”
Section: Methodsmentioning
confidence: 66%
“…The fraction of exact exchange (0.375) adjusted to yield the experimental low temperature bandgap of 3.43 eV for ZnO 19 yields the bandgap of 10.2 eV for BeO, which is close to the experimental value of 10.6 eV, 20 and 7.72 eV for the stable rock-salt phase of MgO, close to the measured bandgap of 7.7 eV. 21 Based on the good agreement of calculated bulk binary bandgaps with experiment, a common value of 0.375 was adopted in this work for the exact exchange 22 fraction with the expectation that reasonable All calculations were performed using supercells with 72 atoms and using C-point eigenvalues only, and projector augmented wave (PAW) pseudopotentials. Wurtzite lattice was used throughout the work for all alloy compositions, which leads to an additional error at high concentrations of Mg, where rock-salt crystal structure would prevail.…”
Section: Methodsmentioning
confidence: 66%
“…The calculations in panel c suggest that across the charge density range studied, the full-width half-maximum (FWHM) of the wavefunction is less than 10 nm, in agreement with previous experiments and theoretical calculations. 8,18,19 In summary, low temperature PL and reflectance spectra of Mg x Zn 1-x O/ZnO HJ reveal several interband optical transitions connected with the lowest two 2DES subbands and the A-and B-valence bands. In the studied 2DES density range of 2.0-6.5 Â 10 11 cm À2 , the first excited electron subband was shown to lie above E F of the 2DES, and therefore, electrons reside only in the lowest subband.…”
mentioning
confidence: 90%
“…[2][3][4][5] In contrast to the Al x Ga 1-x As/GaAs (x > 0.2) heterointerface where the presence of a large barrier height in combination with modulation doping determines both the energy band diagram and electron distribution between different quantized subbands of the 2DES, 6,7 it is the discontinuity in internal polarization at the Mg x Zn 1-x O/ ZnO heterointerface that naturally induces a 2DES. 8 The charge density (n) is therefore determined by the discontinuity in electric field, which is a monotonic function of Mg-fraction. 2 However, the barrier height too grows linearly with Mg-content x.…”
mentioning
confidence: 99%
“…[17][18][19] In the Zn 1−x Mg x O/ZnO HS system, the polarization-induced internal electrostatic filed produces and confines the uncompensated bound charge at the interface, forming the 2DEG. [20] In addition to these three mechanisms, several other factors such as oxygen vacancies [21][22][23][24][25] and cation intermixing [14,26] were also proposed to be able to produce metallic states. For instance, it was recently revealed that tuning redox reactions on the surface of STO substrate might be one approach to produce oxygen vacancies and the resulting interfacial conductivity.…”
Section: Introductionmentioning
confidence: 99%